Covalent organic framework with electrodeposited copper nanoparticles - a desirable catalyst for the Ullmann coupling reaction - Chandran, Chandana; Singh, Himan Dev; Leo, Liya S.; Shekhar, Pragalbh; Rase, Deepak; Chakraborty, Debanjan; Vinod, Chathakudath P.; Vaidhyanathan, Ramanathan (Journal of Materials Chemistry A, 2022)
A covalent organic framework is a porous covalently-linked polymeric assembly built from molecular lego blocks, the monomers. A COF's high surface area, ordered pores, and intrinsic low density makes it a perfect heterogeneous catalyst component. Dispersing catalytic metal nanoparticles into the porous COF matrix in a `capping-agent-free' manner can aid the maximal utilization of the active sites. To generate single-site catalysts, metals have been anchored to dense supports, or metal ions have been coordinated to the porous organic framework. The latter has superior atom efficiency and a substrate diffusion advantage. Stably nestling neutral metallic clusters into open-framework supports with no specifically strong binding groups requires a different approach. If infused from extremely dilute electrolytes, metal clusters can be nanoconfined into electrically activated COFs. At low-loadings, it can resemble a single-site catalyst with high atom efficiency. Herein, we report the larger scale synthesis of IISERP-COF15 and electrochemical loading of copper nanoparticles into its pores at loadings as low as 3.34 wt%. We employed classical Ullmann reactions to adjudge its activity. Typical turnover numbers for the catalysts reported in the literature are approximately 50-100. A Cu@COF shows high activity with a very low catalyst loading of 0.25 mol% (TON around similar to 300-350 vs. 4 for neat CuCl2 center dot 2H(2)O (homogeneous catalyst) and turnover frequency (similar to 15-17 h(-1))). We recycled it for up to 3 cycles. Furthermore, we report a multi-fold Ullmann reaction producing an unreported hexaaldehyde to demonstrate the latitude of the catalyst. Our work points to the potential of a dilutely loaded metal@COF as a mimic of the single-site catalyst for synthesizing valuable C-O linked molecules. Our findings from computational modeling shed light on the role of the COF as an active nanoporous support for Ullmann C-O coupling.

COF-supported zirconium oxyhydroxide as a versatile heterogeneous catalyst for Knoevenagel condensation and nerve agent hydrolysis - Shekhar, Pragalbh; Devulapalli, Venkata Swaroopa Datta; Reji, Reshma; Singh, Himan Dev; Jose, Aleena; Singh, Piyush; Torris, Arun; Vinod, Chatakudath P.; Tokarz III, John A.; Mahle, John J.; Peterson, Gregory W.; Borguet, Eric; et al. (iScience, 2023)
A composite of catalytic Lewis acidic zirconium oxyhydroxides (8 wt %) and a covalent organic framework (COF) was synthesized. X-ray diffraction and infrared (IR) spectroscopy reveal that COF's structure is pre-served after loading with zirconium oxyhydroxides. Electron microscopy confirms a homogeneous distri-bution of nano-to sub-micron-sized zirconium clusters in the COF. 3D X-ray tomography captures the micron-sized channels connecting the well-dispersed zirconium clusters on the COF. The crystalline ZrOx(OH)(y)@COF's nanostructure was model-optimized via simulated annealing methods. Using 0.8 mol % of the catalyst yielded a turnover number of 100-120 and a turnover frequency of 160-360 h(-1) for Knoevenagel condensation in aqueous medium. Additionally, 2.2 mol % of catalyst catalyzes the hy-drolysis of dimethyl nitrophenyl phosphate, a simulant of nerve agent Soman, with a conversion rate of 37% in 180 min. The hydrolytic detoxification of the live agent Soman is also achieved. Our study unveils COF-stabilized ZrOx(OH)(y) as a new class of zirconium-based Lewis + Bronsted-acid catalysts.